Clickbait Headline in News of Online Prostitution Case - Olivia Lewi Pramesti (Jurnal Pekommas, 2020)
The increase of internet use triggers online media industry to compete for attracting readers. One of the ways is using the clickbait headline in the news. The clickbait is a catchy headline that attracts the readers to click on the news. This study aims to look at the tendency of clickbait title patterns in criminal news, namely online prostitution cases. The research method is quantitative content analysis. The news that will be examined is the news of Vanessa Angel's online prostitution case on Tribunnews.com for the period of January to June 2019. The result shows that Tribunnews.com applies the pattern of the clickbait headline in Vanessa Angel's news.